Prediction And Correlation Of Computed Tomography Findings With First Clinical Presentation in patients diagnosed Primary Brain Tumour. - Abdullah, Mohd Shafie (2001)
The brain tumour is increasing in incidence nowadays probably with the availability of new high technology facilities such as computed tomography, magnetic resonance imaging and angiogarphy. There is a wide spectrum of presentation of patients in tenn age and clinical presentations. An early detection of the tumours will generally give a better outcome with the availability of neurosurgeons and neuroimaging facilities. Neuroimaging play an important role in detecting the lesion ,hence to reduce the morbidity and mortality.